TRADISI MENGHAFAL AL-QUR’AN DALAM MASYARAKAT BENDA SIRAMPOG BREBES - Zubaidah, Aisyah; Mutammam, Mutammam (Sabda: Jurnal Kajian Kebudayaan, 2016)
The tradition of memorizing the holy Quran cannot be separated from the people of Benda, Sirampog. For them, memorizing the holy Quran is a thariqoh (a particular way) to be a lofty man to get close to God (Allah). This tradition is inherited from family institution and teacher-student circle. This research shows that when this tradition creates a group of people who memorized Quran, the organization of Quran memorizer in one organization has a positive impact for their existence. Through this organization, they have a chance to develop a social and economic network to empower themselves. As a result, their opportunity to get a social and economic benefit is bigger than before. This research also found that, the power of a leader of this organization can support and facilitate the life of the tradition of Quran memorizer